The associations of cash transfers and childcare for the development of children born to adolescent and young mothers in South Africa - Tatham, Claire (School of Economics, 2026)
Exposure to adversities strongly predicts early childbearing among adolescent girls and young women. Early motherhood is associated with negative effects on their children's developmental outcomes, but the factors contributing to the well-being of children born to adolescent mothers remain uncertain. The Child Support Grant (CSG) emerges as a potential avenue of support. This paper analysed cross-sectional data of adolescent mother-child dyads (N =1,046 mothers; 1,144 children) from the Eastern Cape of South Africa, collected between 2017 to 2019. Adolescent and young mothers (aged 10-19 at the birth of their first child) completed questionnaires on their well-being and health. The Mullen Scales of Early Learning Composite Score was used to measure children's cognitive performance in expressive language, receptive language, visual reception, and fine motor domains. This study assessed factors associated with CSG receipt and early CSG receipt. Additionally, this study tested the association between CSG receipt and child development, and the moderating role of formal childcare. The results reveal socioeconomic factors such as having sibling, low maternal education and caregiver support to influence CSG access and timeliness. Moreover, both early CSG receipt and formal childcare had a significant positive effect on child development. To ensure timely access to CSG receipt, SASSA offices should run outreach campaigns targeting first-time adolescent mothers with low levels of education and intervention promoting caregiver support. There is also a need to develop flexible CSG policies that recognise the essential role of different family members and provide additional support. Social protection systems for children of adolescent mothers requires approaches that acknowledge the role of maternal human capital development in determining child outcomes and takes advantage of age-related opportunities for intervention.